Construction of a novel INHIBIT logic gate through a fine-tuned assembly of anthryl fluorophores via selective anion recognition and host–guest interactions. Issue 1 (22nd December 2015) - Zhang, Lei; He, Yilong; Zhang, Na; Liu, Daosheng; Han, Jiao; Gong, Weitao
Abstract : A novel ligand containing of anthryl fluorophore was achieved. The assembly and disassembly of anthryl fluorophore by Pi and β-CD as chemical inputs and emission around 500 nm as output resulted in the construction of novel INHIBIT gate. Abstract : A novel ligand (AAP ) based on an anthryl fluorophore was rationally designed and synthesized. The presence of H2 PO4 − (Pi) could induce the effective assembly of the ligand which leads to a strong excimer emission, while β-cyclodextrin (β-CD) disassembled the Pi–ligand complex through a host–guest interaction with terminal adamantane groups. This disassembly causes a considerable decrement in emissive intensity as well as a clear blue-shift in emissive wavelength. By manipulating the assembly and disassembly of anthryl fluorophores with Pi and β-CD, a novel INHIBIT logic gate was constructed using Pi and β-CD as the chemical inputs and fluorescence emission as the output.